Polymer-Based Scaffold Strategies for Spinal Cord Repair and Regeneration - Qu, Wenrui; Chen, Bingpeng; Shu, Wentao; Tian, Heng; Ou, Xiaolan; Zhang, Xi; Wang, Yinan; Wu, Minfei (Frontiers in Bioengineering and Biotechnology, 2020)
The injury to the spinal cord is among the most complex fields of medical development. Spinal cord injury (SCI) leads to acute loss of motor and sensory function beneath the injury level and is linked to a dismal prognosis. Currently, while a strategy that could heal the injured spinal cord remains unforeseen, the latest advancements in polymer-mediated approaches demonstrate promising treatment forms to remyelinate or regenetrate the axons and to integrate new neural cells in the SCI. Moreover, they possess the capacity to locally deliver bioactive substances, synergistic cells and/or growth factors therapies, which play a critical role in neuroprotection and neuroregeneration. Here, we provide an extensive overview of the SCI characteristics, the pathophysiology of SCI, and strategies and challenges for the treatment of SCI in a review. This review highlights the recent encouraging applications of polymer-based scaffolds in developing the novel SCI therapy.